PENGARUH SISTEM OLAH TANAH DAN PEMBERIAN MULSA ORGANIK TERHADAP ALIRAN PERMUKAAN DAN EROSI PADA PERTANAMAN KACANG HIJAU (Vigna radiata) MUSIM TANAM KE EMPAT DI LABORATORIUM LAPANG TERPADU FAKULTAS PERTANIAN UNIVERSITAS LAMPUNG - Jaya, Ahmad Shan Kemala; Banuwa, Irwan Sukri; Novpriansyah, Hery; Utomo, Muhajir (Jurnal Agrotek Tropika, 2020)
Tillage can significantly affect soil susceptibility to erosion which can accelerate and increase the rate of erosion. The use of mulch can reduce erosion by reducing the impact energy of falling rain so it does not damage the structure and aggregate of the soil, reducing speed, volume and scouring of surface runoff. This study aims to determine the effect of (1) tillage systems on surface runoff and erosion in green bean plant (2) applying organic mulch to the amount of surface runoff and erosion in green bean plant (3) the interaction between the tillage system and the use of mulch on surface runoff and erosion in green bean plant . This research was conducted in March to June 2017 in the Integrated Field Laboratory of the Faculty of Agriculture, University of Lampung. The design used is factorial in the Complete Randomized Block Design (RCBD) on two treatment factors namely the tillage system and the mulch with four replications. The results showed that the tillage system did not significantly affect all observed variables. In the treatment of giving and without mulch also did not significantly affect all observed variables. The response of surface runoff and erosion in green bean plant to the tillage system does not depend on the organic mulch shown on all variables.